MAKNA KOMUNIKASI NONVERBAL SENI PERTUNJUKAN JARAN KEPANG TURONGGO PUTRO DI BAGAN BATU KABUPATEN ROKAN HILIR - Sari, Mustika Mala; Yohana, Nova (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In Indonesia, art performance is one of culture which must be preserved by every people. One of the examples is society in Bagan Batu where transmigrant people are always preserving Jaran Kepang. Jaran Kepang Turunggo Putro art has verbal and nonverbal communication aspect which has various meaning. The purpose of this research is to know the messages of kinesics meaning, artifactual meaning and smelling meaning in this show of Jaran Kepang Turunggo Putro in Bagan Batu.This research was used qualitative method in symbolic theory. Subjects of this research are players, trainers, and some figures of Jaran Kepang Turunggo Putro in Bagan Batu who have choose by using Purposive technique and also audiences by using Accidental way. The collecting data technique was done by using observation, interview and documentation.The result of this research was showed the kinesics meaning of players in Jaran Kepang Turunggo Putro in Bagan Batu. It consists of facial messages which has seriously meaning and focus on showing, and in gestural and postural meaning, it has movement of kuda kepang dance which has meaning of a soldier in a horse for war, reog and ganongan movement which has meaning of king entertainer in a kingdom, and petilan puppet movement has meaning of two puppets in fighting a kingdom. Artifactual meaning of Jaran Kepang Turunggo Putro is in clothing and cosmetics. Clothing has character signed meaning for every player in Jaran Kepang show and cosmetics have unknowing signed meaning (pangling) for audiences to hide players real face and showing a strong and characterized a good player. Smelling messages is as a media of sending messages to God for permission to ancestors in doing their best performance.Keywords: Jaran Kepang, Nonverbal communication, symbolic interactions